2014
DOI: 10.1186/s13028-014-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ossificated ungular cartilages regarding the performance of cold-blooded trotters

Abstract: BackgroundOssification of the ungular cartilages (OUC) in the foot of horses has been studied for more than 100 years. There is a high heritability of this condition but its clinical relevance has remained questionable. Nevertheless, modern equine orthopedic literature ranks OUC as one of top 10 causes of lameness in cold-blooded trotters and stallions of these breeds are excluded from breeding if they have more than mild levels of side bones. Cold-blooded trotters have been used for racing for many decades an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…ossification. Besides the obvious need to standardize the radiological examination technique, we believe that using our more forgiving new scale approach is beneficial in clinical practice, especially since our recent studies [ 27 ] indicated that OUC had no effect on performance in cold-blooded trotters and since field radiography, unfortunately, often is performed under non optimized circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ossification. Besides the obvious need to standardize the radiological examination technique, we believe that using our more forgiving new scale approach is beneficial in clinical practice, especially since our recent studies [ 27 ] indicated that OUC had no effect on performance in cold-blooded trotters and since field radiography, unfortunately, often is performed under non optimized circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience shows that radiological examination technique and artifacts such as small amounts of mud on hooves might both affect the number of separate centers of ossification found in a population. However, the fact that we had this problem on two radiographs did not alter the result that presence of separate centers of ossification does not affect the performance of the horse [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Проблематику окостеніння суглобових хрящів вивчають вже більше 100 років та доведено, що це явище може мати спадковий прояв або бути наслідком травмування. Дані стосовно кореляції ступеня осифікації у межах суглоба та зниженням продуктивності тварини відсутні [30,31]. Проте наявність осифікації у скакальному суглобі в більшості випадків стає причиною остеоартриту цього суглоба [32].…”
Section: державний біотехнологічний університетunclassified